The Practical Importance And Relevance Of Teaching Folk Epics - Olimov, Shodmon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article examines the importance of in-depth study of the great immortal epic of our people "Alpomish" and teaching it to the younger generation, through which the genre nature and artistic and compositional features of folk epics, educational value, respect for the national heritage are revealed. values, dedication, the idea of education, the expression of traditions and customs inherited from our ancestors, preservation, encouragement to collect and learn.